REMOTE AUDIT: BAGAIMANA PENGALAMAN AUDITOR DAN TIME BUDGET PRESSURE MEMPENGARUHI KUALITAS AUDIT DI SEKTOR KELAPA SAWIT: REMOTE AUDIT: HOW DO AUDITOR EXPERIENCE AND TIME BUDGET PRESSURE INFLUENCE AUDIT QUALITY IN THE PALM PALM SECTOR - Azhhar, M. Indra; Reskino, Reskino (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This research seeks to explore various factors that influence audit quality within the Public Accounting Firm (PAF). This study specifically focuses on the impact of work experience, time budget pressure , and the moderating effect of remote auditing on audit quality. To achieve this goal, a quantitative approach was carefully applied, using a carefully selected sample of 100 auditors from DKI Jakarta through a purposive sampling method. Intricate relationships between variables are revealed with the help of advanced Structural Equation Modeling (SEM) and PLS analysis techniques. The main of this study, work experience and time budget pressure , both show a positive influence on audit quality, underscoring their importance in ensuring high-quality audits. By highlighting the importance of work experience and appropriate time allocation, these findings underscore the importance of KAPs prioritizing the location and retention of experienced auditors while ensuring adequate time allocation for audit completion. Additionally, the absence of a moderating effect of remote auditing suggests that companies have the potential to implement remote work arrangements without compromising audit quality, provided experienced auditors are assigned and appropriate time management practices are diligently adhered to.